Integrated agronomic, physiological, microstructure, and whole-transcriptome analyses reveal the role of biomass accumulation and quality formation during Se biofortification in alfalfa - Wang, Qingdong; Hu, Jinke; Lou, Tongbo; Li, Yan; Shi, Yuhua; Hu, Huafeng (Frontiers in Plant Science, 2023)
Se-biofortified agricultural products receive considerable interest due to the worldwide severity of selenium (Se) deficiency. Alfalfa (Medicago sativa L.), the king of forage, has a large biomass, a high protein content, and a high level of adaptability, making it a good resource for Se biofortification. Analyses of agronomic, quality, physiological, and microstructure results indicated the mechanism of biomass increase and quality development in alfalfa during Se treatment. Se treatment effectively increased Se content, biomass accumulation, and protein levels in alfalfa. The enhancement of antioxidant capacity contributes to the maintenance of low levels of reactive oxygen species (ROS), which in turn serves to increase alfalfa's stress resistance and the stability of its intracellular environment. An increase in the rate of photosynthesis contributes to the accumulation of biomass in alfalfa. To conduct a more comprehensive investigation of the regulatory networks induced by Se treatment, the transcriptome sequencing of non-coding RNA (ncRNA) was employed to compare 100 mg/kg Se treatment and control groups. The analysis identified 1,414, 62, and 5 genes as DE-long non-coding RNAs (DE-lncRNA), DE-microRNAs (DE-miRNA), and DE-circular RNA (DE-circRNA), respectively. The function of miRNA-related regulatory networks during Se biofortification in alfalfa was investigated. Subsequent enrichment analysis revealed significant involvement of transcription factors, DNA replication and repair mechanisms, photosynthesis, carbohydrate metabolism, and protein processing. The antioxidant capacity and protein accumulation of alfalfa were regulated by the modulation of signal transduction, the glyoxalase pathway, proteostasis, and circRNA/lncRNA-related regulatory networks. The findings offer new perspectives on the regulatory mechanisms of Se in plant growth, biomass accumulation, and stress responses, and propose potential strategies for enhancing its utilization in the agricultural sector.